The Relationship Between Health Belief Model (HBM) And Female Adolescents' Compliance In Consuming Fe Tablets In The Working Area Of Uptd Padang Cermin Health Center, Pesawaran District, 2024 - Ririn Eka Yuliani; Desi Kumalasari; Nopi Anggista; Riona Sanjaya (Sean Institute, 2024)
The nutritional problem often experienced by female adolescents is iron deficiency, making adolescent girls during puberty at high risk of iron deficiency anemia. The anemia prevention efforts carried out so far by health workers at Padang Cermin Health Center is the provision of Fe tablets targeting female adolescents aged 12-18 years. Although Fe tablets have been provided, the results of Hb screening in 2023 showed 26.2% with an average Hb level of 9.8 g/dl, categorized as anemic. The research objective was to determine the relationship between HBM and female adolescents' compliance in consuming Fe tablets. This is a quantitative research, with an analytical research design using a cross-sectional approach. The research was conducted from August 1-30, 2024, at 6 adolescent Integrated Service Posts in the working area of UPTD Padang Cermin Health Center. The population consisted of all female adolescents aged 12-18 years totaling 346 people, with a sample size of 78 people. The sampling technique used was stratified random sampling. Data analysis used the chi-square test. The research results showed that the frequency distribution of female adolescents' HBM was higher in the poor category at 51 people (65.4%), and the frequency distribution of female adolescents' compliance in consuming Fe tablets was higher in the non-compliant category at 48 people (61.5%). Chi-square test results showed there is a relationship between HBM and female adolescents' compliance in consuming Fe tablets (p-value = 0.012 < 0.05). Health workers should be more active in socializing key messages that anemia can be controlled if compliant in consuming Fe tablets regularly, which can be disseminated through social media channels, school counseling, or adolescent integrated service posts using fun game methods to make socialization more attractive according to adolescent characteristics.